Prevention of Stunting by Providing Knowledge to Youth about the Impact of Early Marriage in Tayan Village, Sanggau Regency, West Kalimantan - Devy Putri Nursanti; Renny Nadeak; Dewi Sartika; Sriwaty Siregar; Siti Ikhsani Ramadhani; Novita Sari; Evi Nur Widya (Universitas STRADA Indonesia, 2024)
Stunting is a condition where human height is less than normal according to gender and age. The effects of stunting last a lifetime and even have an impact on the next generation and hampered development in terms of motor, verbal and cognitive. To prevent stunting, you can do socialization on the dangers of early marriage. The target of this activity is students who are in junior high school. The purpose of holding this activity is to increase students' understanding of the risks of the dangers of early marriage which is one of the factors causing stunting. The method used in this activity is counseling or socialization with data collection techniques in the form of observation and pre-test with the aim of determining whether or not socialization activities are necessary. Data analysis was carried out on the results of the pre-test and post-test to determine whether there was a change in understanding of the dangers of early marriage and stunting. In addition, the data was also analyzed to determine students' interest in engaging in early marriage. The results of this activity indicate that the implementation of socialization on the impact of early marriage at SMK Cahaya has an effect on increasing students' understanding of the dangers of early marriage and the risk of impacting stunting.